Attosecond-controlled photoemission from metal nanowire tips in the few-electron regime - Ahn, B.; Schoetz, J.; Kang, M.; Okell, W. A.; Mitra, S.; Foerg, B.; Zherebtsov, S.; Suessmann, F.; Burger, C.; Kuebel, M.; Liu, C.; Wirth, A.; et al. (APL Photonics, 2017)
Metal nanotip photoemitters have proven to be versatile in fundamental nanoplasmonics research and applications, including, e.g., the generation of ultrafast electron pulses, the adiabatic focusing of plasmons, and as light-triggered electron sources for microscopy. Here, we report the generation of high energy photoelectrons (up to 160 eV) in photoemission from single-crystalline nanowire tips in few-cycle, 750-nm laser fields at peak intensities of (2-7.3) × 1012 W/cm2. Recording the carrier-envelope phase (CEP)-dependent photoemission from the nanowire tips allows us to identify rescattering contributions and also permits us to determine the high-energy cutoff of the electron spectra as a function of laser intensity. So far these types of experiments from metal nanotips have been limited to an emission regime with less than one electron per pulse. We detect up to 13 e/shot and given the limited detection efficiency, we expect up to a few ten times more electrons being emitted from the nanowire. Within the investigated intensity range, we find linear scaling of cutoff energies. The nonlinear scaling of electron count rates is consistent with tunneling photoemission occurring in the absence of significant charge interaction. The high electron energy gain is attributed to field-induced rescattering in the enhanced nanolocalized fields at the wires apex, where a strong CEP-modulation is indicative of the attosecond control of photoemission.
CRIS-Team Scopus Importer:2023-04-20